2021
DOI: 10.3390/life11070670
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light in Dermatology

Abstract: Phototherapy is an important method of dermatological treatments. Ultraviolet (280–400 nm) therapy is of great importance; however, there are concerns of its long-term use, as it can lead to skin aging and carcinogenesis. This review aims to evaluate the role and the mechanism of action of blue light (400–500 nm), a UV-free method. The main mediators of cellular responses to blue light are nitric oxide (NO) and reactive oxygen species (ROS). However, the detailed mechanism is still not fully understood. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 70 publications
1
29
0
2
Order By: Relevance
“…The blue light therapy is suitable for treating acne and killing bacteria on the skin layer. Sadowska et al [5], Diogo et al [6], and Opel et al [7] stated a large number of documented reviews related to the use of blue LEDs phototherapy and they confirmed the conclusive findings that the light from blue LEDs (405-420 nm) was effective in mild to moderate inflammatory of the face treatment of the acne vulgaris and P.acne. In addition, some data [6], [7] indicated that light from the blue LEDs (400-470 nm) may also help treat the acne and P.acne.…”
Section: Introductionmentioning
confidence: 84%
“…The blue light therapy is suitable for treating acne and killing bacteria on the skin layer. Sadowska et al [5], Diogo et al [6], and Opel et al [7] stated a large number of documented reviews related to the use of blue LEDs phototherapy and they confirmed the conclusive findings that the light from blue LEDs (405-420 nm) was effective in mild to moderate inflammatory of the face treatment of the acne vulgaris and P.acne. In addition, some data [6], [7] indicated that light from the blue LEDs (400-470 nm) may also help treat the acne and P.acne.…”
Section: Introductionmentioning
confidence: 84%
“…The principal differences in the effects of various wavelengths of light on generation of ROS in the skin are the chromophores that mediate radical production. Light-absorbing chromophores in the skin include nucleic acids, aromatic amino acids, urocanic acid, NADH and NADPH, cytochromes, riboflavins, porphyrins, melanin and its precursors, and βcarotene [68]. These chromophores can act as photosensitizers that catalyze the generation of ROS and reactive nitrogen species that, if not quenched by cellular antioxidant defenses, can damage sensitive biomolecules such as DNA, RNA, proteins and lipids.…”
Section: Limitations In the Use Of Sunscreen For Photoprotectionmentioning
confidence: 99%
“…Considerable research showed that phototherapy based on blue light has produced beneficial consequences such as treatment of neonatal jaundice ( 123 125 ), regulation of melatonin and circadian rhythm ( 126 128 ), anti-inflammation ( 129 – 131 ), immunomodulation ( 132 ), wound healing ( 133 135 ), tissue regeneration, and anticancer therapies ( 103 , 114 , 133 , 136 ). Furthermore, blue light reduced the follicular colonization of Propionibacterium acnes by activating the endogenous bacterial porphyrin and inhibiting acne development, while possibly interfering with lipogenesis in adipocytes and suppressing sebum formation for acne treatment ( 137 ).…”
Section: Blue Light Photobiomodulation Therapy In Cancer Treatmentmentioning
confidence: 99%
“…Blue light, as a visible light with a wavelength range of 400–500 nm, has been clinically applied successfully comprising neonatal jaundice, psoriasis (Pv), atopic dermatitis (AD), eczema, acne, and other inflammatory skin conditions, although the number of available clinical studies evaluating the efficacy of blue light treatment is still limited ( 103 , 136 ). Furthermore, recent studies have demonstrated that blue light irradiation inhibits the proliferation of multiple types of cancer cells in vitro and in vivo , including colon cancer cells ( 14 , 144 , 145 ), malignant glioma cells ( 12 ), melanoma cells ( 10 , 146 , 147 ), B-cell lymphoma cells ( 13 ), fibrosarcoma cells ( 14 ), pancreatic cancer cells ( 15 ), cutaneous squamous cell carcinoma cells (CSCC), epidermoid carcinoma cells ( 148 , 149 ), leukemia cells (Kasumi-1) ( 150 ), bladder cancer cells ( 151 ), colorectal cancer cells ( 152 , 153 ), breast cancer cells ( 91 ), and human OS cells ( 95 , 98 ).…”
Section: Blue Light Photobiomodulation Therapy In Cancer Treatmentmentioning
confidence: 99%